THE EFFECTS OF MARKETING MIX ON PESTICIDE PURCHASING DECISIONS THROUGH BRAND IMAGE AMONG RICE FARMERS IN KANOR SUB-DISTRICT, BOJONEGORO DISTRICT - Sari, Betty Nur Indah; Setiawan, Budi; Riana, Fitria Dina (Socio-Economics/Agribusiness Department, 2024)
One of the regencies in East Java, Bojonegoro Regency, also relies on the agricultural sector to drive the economy after the oil and gas sector. One of the sub-districts that has productive land with a high contribution to rice production is Kanor sub-district. Because it is located on the banks of the Bengawan Solo river, the land in the sub-district is often threatened by pest attacks and affected by flooding. In an effort to prevent and treat pests, rice farmers in Kanor Sub-district choose to use pesticides because it is easier. Without the use of pesticides, the damage caused by pests causes a threat that suppresses rice productivity. On the other hand, the use of chemical pesticides without strict control and guidance also poses risks to the health of the population and the environment as well as damage to paddy fields due to nutrient depletion. Therefore it is important for farmers to choose the right pesticide product so as not to cause losses. Farmers' decisions to buy pesticide products are influenced by several different preferences, but specifically an important factor in influencing purchasing decisions is the marketing mix carried out by pesticide producers. On the basis of these findings, this study adopts the marketing mix variable as a predictor to explain farmers' pesticide purchasing decisions. The marketing mix referred to in this study is product quality, price, place and promotion. This research is expected to be one of the means for companies engaged in pesticide products in predicting the marketing mix which is often an important factor for farmers in deciding to choose pesticide products.